EFFECT OF GOLD AND NICKEL NANOPARTICLES ON IMMUNE PROTEINS OF TOXOPLASMOSIS PATIENTS - A Abdulsattar, Sura; H Drywall, Abdullah (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: An interaction between a nanoparticle and the immune system is considered desirable when it may lead to various beneficial medical applications such as vaccines, delivery of drugs, antigens or therapeutics for inflammatory and autoimmune disorders. This study aims to evaluate the impact of some immune proteins by the presence of gold and nickel nanoparticles in sera of toxoplasmosis patients. Methods: A total of 20 patients women with toxoplasmosis aged (20-40 year) attending Central Health Laboratory in Baghdad city for the period (November 2016 to February 2017) and 20 age-matched of women healthy as a control were included in this study. Results: A non-significant increase in the activity and specific activity of protease in the sera of women infected with toxoplasmosis were observed in comparison to their values in the healthy (pËƒ0.05). While a non-significant decrease in total protein values was reported. The results of effect of nanoparticles showed a decrease in the level of the enzyme in the presence of nanoparticles by 41.3%, while the results showed that inhibition of nickel nanoparticles was greater and 43.8%. The results indicated that IgA, IgG, and IgM levels were decreased in the presence of gold nanoparticles. In the same context, both IgA and IgG were shown to be inhibitory in the presence of nickel nanoparticles while the results showed activation of the IgM level with nickel nanoparticles. Conclusion: We conclude from this study that other studies are required to confirm our results and therefore support the possibility of using nickel nanoparticles as a support for the treatment of toxoplasmosis through its dual effect first by reducing the protease, which is essential for survival of the parasite and second by activating IgM level, which enhances the immune defense of the body against the parasite.